Broken blossoms a tale of forbidden love = Broken blossoms or The yellow man and the girl = Eine Blüte gebrochen - Gish, Lillian 1893-1993; Barthelmess, Richard 1895-1963; Crisp, Donald 1882-1974; Howard, Art; Bitzer, G. W. 1872-1944; Burke, Thomas (Alpha Video Distributions Inc., 2005)
Presents a tender yet tragic tale of love and suffering in the seedy Limehouse district of London. A young Chinese man hopes to spread the peaceful philosophy of his Eastern religion. He befriends a frail waif who is abused by her brutal boxer father
Stummfilm, Orig.: USA, 1919
Keywords: Stummfilm; Kulturkonflikt; Fathers and daughters / Drama; Death / Drama; Revenge / Drama; Chinese / England / London / Drama; Abused children / England / London / Drama; Culture conflict / England / London / Drama; Child abuse / England / London / Drama; Racism in motion pictures / Drama; Ethnic relations / Drama; London (England) / Ethnic relations / Drama; Abused children; Child abuse; Chinese; Culture conflict; Death; Ethnic relations; Fathers and daughters; Racism in motion pictures; Revenge; England / London; Father-daughter relationship / Drama; DVD-Video discs; Drama; Feature films; Fiction films; Silent films; Film adaptations; Film; DVD-Video